(untitled) (Journal of Comilla Medical College Teachers’ Association, 2024)
Rhinosporidiosis is a chronic granulomatous disease caused by the fungus commonly affecting anterior nares and nasopharynx. Other sites of involvement included the larynx, hard palate, vagina, vulva, and anus. It may occur very rarely at urethra. This disease generally acquired by bathing in ponds contaminated by animal feces. It is a benign condition where the organisms are limited to the lesion and regional lymph nodes. Adjacent tissues are not usually involved. The infection is very slow to develop with little discomfort; it is often difficult to ascribe age at onset. Males account for 70% to 90% of cases mostly from the rural environment. The lesion causes pressure and obstructive symptoms when they enlarge. Diagnosis usually confirmed by histopathology of excised mass. J Com Med Col Teachers’ Asso July 2023; 27(2): 83-84